On-line implementation of model free controller for oxygen stoichiometry and pressure difference control of polymer electrolyte fuel cell. (9th November 2022) - Ait Ziane, M.; Pera, M.C.; Join, C.; Benne, M.; Chabriat, J.P.; Yousfi Steiner, N.; Damour, C.
Abstract: This paper proposes and validates a model free controller to improve the real time operating conditions of Proton Exchange Membrane Fuel Cells (PEMFC). This approach is based on an ultra-local model that does not depend on a precise knowledge of the system. It is perfectly adapted to a complex system such as the fuel cell, while benefiting from the ease of online implementation and low computational cost. The designed controller is used to regulate both the oxygen stoichiometry and the membrane inlet pressure, which are crucial operating conditions for the fuel cell's lifetime. The objectives of the proposed control strategy are twofold: preventing the starvation failure, and limiting the potential for mechanical degradation of the membrane during a large pressure difference. The performance of the proposed control strategy is initially evaluated by a simulation environment for both oxygen stoichiometry and inlet pressure difference control of fuel cell stack. An online validation on 1.2 KW fuel cell stack is conducted to control the membrane pressure drop. Two case studies are comprehensively investigated in relation to stoichiometry control: set point tracking and rejection of unmeasured disturbances caused by current variations. Simulations and experimental results reveal that the proposed controller provides significantly better performance in terms of fast trajectory tracking, and ensures less overshoot compared to the Fuzzy PID and PID controller. This efficiency is proven using the Integral Absolute Error (IAE), Integral Squared Error (ISE) and Integral of the Square input (ISU) performance indexes. Graphical abstract: Image 1 Highlights: iP and iPD controllers have shown good performance in controlling oxygen stoichiometry and inlet pressure difference. The experimental validation showed a great ability to reduce the inlet pressure difference for different cases studied. The proposed controller offers better performance than the embedded industrial controller and can easily replace it.